Measuring School and Teacher Academic Optimism in Diverse School Contexts The Validation of the adapted Survey for Academic Optimism - Lelieur, R.; Clycq, N.; Vanhoof, J. (Pedagogische Studiën, 2022)
Academic optimism is the reflection of a triadic set of interactions between efficacy, trust, and academic emphasis, which positively correlates with students’ performance, also after controlling for previous performance, SES and other demographic variables. This study focuses on refining and validating existing school and teacher academic optimism questionnaires. Cognitive interviews (n = 5), a pilot study (n = 106) and a large-scale study (n = 1061) were conducted with teachers from urban secondary schools in order to develop a new measurement instrument and test its content, cognitive and construct validity as well as the internal consistency of the individual scales. We provide an in-depth understanding of the underlying constructs and equip academics and  practitioners with a valid aSAO-questionnaire to measure academic optimism, both at the collective school level and at the individual teacher level.